2007
DOI: 10.1016/j.expneurol.2007.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Reinnervation of the tibialis anterior following sciatic nerve crush injury: A confocal microscopic study in transgenic mice

Abstract: Transgenic mice whose axons and Schwann cells express fluorescent chromophores enable new imaging techniques and augment concepts in developmental neurobiology. The utility of these tools in the study of traumatic nerve injury depends on employing nerve models that are amenable to microsurgical manipulation and gauging functional recovery. Motor recovery from sciatic nerve crush injury is studied here by evaluating motor endplates of the tibialis anterior muscle, which is innervated by the deep peroneal branch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
94
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(105 citation statements)
references
References 85 publications
9
94
0
2
Order By: Relevance
“…To facilitate the characterization of axonal injury and degeneration following mild TBI in the infant P7 mouse, we used the progeny of mThy1-YFP16 mouse line (Feng et al, 2000;Magill et al, 2007). In this line yellow fluorescent protein (YFP) is expressed at high levels in many neurons throughout the brain.…”
Section: Topographic Distribution Of Injured Axons In P7 Thy1-yfp16 Mmentioning
confidence: 99%
“…To facilitate the characterization of axonal injury and degeneration following mild TBI in the infant P7 mouse, we used the progeny of mThy1-YFP16 mouse line (Feng et al, 2000;Magill et al, 2007). In this line yellow fluorescent protein (YFP) is expressed at high levels in many neurons throughout the brain.…”
Section: Topographic Distribution Of Injured Axons In P7 Thy1-yfp16 Mmentioning
confidence: 99%
“…In these examples, however, the peripheral target is multiply-innervated by projections from a single axon. During development, axons from multiple neurons compete to maintain synapses with motor endplates (Keller-Peck, et al 2001), while after axotomy, multiple terminal branches from the same axon project to the same endplate (Magill, et al 2007). In the case of ETS repair, however, it is the neuron that has to innervate multiple discrete motor units or other peripheral targets to avoid creating a donor nerve deficit.…”
Section: Discussionmentioning
confidence: 99%
“…150 days after ETS repair, whole EDL specimens were soaked for 30 minutes in a 1:100 solution of Alexa 594-conjugated alpha-bungarotoxin (BTX; Molecular Probes, Eugene, OR). Labeled specimens were surveyed under fluorescent microscopy and regions containing endplates imaged with the confocal microscope with a 40x oil (1.3 N.A) objective using 515 and 561 nm lasers (Magill, et al 2007). Flattened Z-series stacks from 100 randomly sampled areas (100 ”m 2 ) occupied by motor endplates (≄300 endplates per group) were evaluated and the percentage reinnervated calculated.…”
Section: Motor Endplate Evaluationmentioning
confidence: 99%
“…After nerve injury and repair, it has been shown that motor endplates are initially polyinnervated, but that later the motor axon/endplate ratio again returns to a normal 1:1 innervation. 26,34,41 This initial poly-or hyperinnervation may be a mechanism for improving the accuracy of reinnervation. Feedback mechanisms such as treadmill exercise 62 and manual stimulation may influence this selection process.…”
Section: The Course Of the Regenerating Axonmentioning
confidence: 99%
“…2 left) and hyperreinnervation at the motor endplate. 41 In the future these animals may also be used to investigate new strategies to improve axonal regeneration and target reinnervation in vivo, providing the additional advantage that the same animals could be used for analysis with other evaluation methods (such as those mentioned below).…”
mentioning
confidence: 99%